Biomass yield, nutritional composition and silage fermentation characteristics of panicum and pennisetum grasses in the savanna agro-ecological zone of Ghana - Cudjoe, Shedrack; Tenakwa, Afirifa E; Akufo, Mintaah N; Akapali, Maxwell; Ansah, Terry; Jauregui, Rosa; Van Der Hoek, Ringenerus; Yamasi, S.; Cai, Y (2024)
Successful silage production can help overcome seasonal fluctuations in feed quality and improve livestock production efficiency in tropical regions. Fodder yield and nutritional value are crucial when selecting forage varieties suitable for silage. This study investigated two Megathyrsus maximus (formerly Panicum mamximum) cultivars (Mombasa and Massai) and a local Napier grass (Cenchrus purpureus, formerly Pennisetum purpureum) focusing on their biomass yield, nutritional quality, and silage fermentation characteristics.